2022
DOI: 10.3389/fpls.2022.921440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self- and Inter-Cultivar Grafting on Growth and Nutrient Content in Sweet Basil (Ocimum basilicum L.)

Abstract: Vegetable grafting has been applied to fruiting crops, yet only to a limited extent in leafy greens and herbs which may also benefit from grafting. In this study, we examined the effect of reciprocal grafting two sweet basil (Ocimum basilicum L.) cultivars of differing vigor on plant growth and leaf mineral nutrient concentration to test whether differences in growth exist due to grafting and whether such differences are due to altered plant nutrient status in two trials. Two cultivars ‘Nufar’ (NU), a high vig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(79 reference statements)
0
2
1
Order By: Relevance
“…By contrast, as mentioned before, other genotypes including accessions from other species like C. chinense U26484 and C. baccatum U27610, showed a similar performance as rootstocks than 'Herminio' itself. Although other authors have not reported significant decreases in the yield of self-grafted varieties (Hollick and Kubota, 2022), our results suggest that, in the case of some varieties of peppers, self-grafting may provoke injuries in the rootstock-scion connection, while paradoxically other materials used as rootstocks may show better compatibility by providing a higher efficiency in restoring the phloem and xylem and then promoting a better mobilization of water and nutrients (Ropokis et al, 2019).…”
Section: Productivity Traitscontrasting
confidence: 69%
“…By contrast, as mentioned before, other genotypes including accessions from other species like C. chinense U26484 and C. baccatum U27610, showed a similar performance as rootstocks than 'Herminio' itself. Although other authors have not reported significant decreases in the yield of self-grafted varieties (Hollick and Kubota, 2022), our results suggest that, in the case of some varieties of peppers, self-grafting may provoke injuries in the rootstock-scion connection, while paradoxically other materials used as rootstocks may show better compatibility by providing a higher efficiency in restoring the phloem and xylem and then promoting a better mobilization of water and nutrients (Ropokis et al, 2019).…”
Section: Productivity Traitscontrasting
confidence: 69%
“…The total antioxidant activity was measured according to Ertani et al The content of the hormones was measured according to Yan et al The N, P, and K contents were measured according to Kubota and Hollick …”
Section: Methodsmentioning
confidence: 99%
“…The total antioxidant activity was measured according to Ertani et al 10 The content of the hormones was measured according to Yan et al 11 The N, P, and K contents were measured according to Kubota and Hollick. 12 RNA Isolation and Transcriptome Sequencing. Total RNA was extracted from tissues using TRIzol reagent, and genomic DNA was removed using DNase I (Takara) according to the manufacturer's (Invitrogen) instructions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%